To Be or Not to Be on Social Media: How Social Media Content Impacts Recruitment - Baker, Edmund; Grimm, Veronika; Ofek-Shanny, Yuval (2023)
This paper extends the literature studying the effect of social media content on the evaluation of job candidates. In a large-scale online experiment that resembles real-life screening of candidates for a job in the hospitality sector, we find that information available on social media through hashtags and liked pages can have a crucial effect on a candidate's chances of obtaining a good rating. Candidates with social media content indicating mental health problems receive lower ratings by an amount equivalent to the effect of having three years on-the-job experience. Interestingly, candidates with no social media profile receive even lower ratings than candidates with mental health problems. In addition, unappealing social media content leads to the strongest reduction in ratings, equivalent to the value of nine years of on-the-job experience. These results demonstrate social media's substantial and likely increasing role in the hiring process.<br
Keywords: Recruitment; Online Experiment; Social Media; Mental Health; Employment Gap; Diskriminierung